(untitled) - West, Lucy (New York, 2001)
Leadership is currently one of the most hotly discussed topics in business. This is the first book to not only identify the characteristics of successful leadership but to show how these qualities can be developed.The Reflecting Glass surveys the field of executive coaching, including its origins, the theoretical framework underpinning it, the forms it can take and the value it adds.Based on the experience of two leading practitioners and with contributions from other key players it provides a detailed methodology for working one-to-one with people at the top of organisations in order to help them become fully effective. Executive coaching has experienced exponential growth over the last five years but as yet there has been little critical appraisal of the activity. This book provides that critique. By describing and benchmarking good practice, The Reflecting Glass will be a valuable tool for those in leadership positions considering executive coaching for themselves, as well as the HR professional.
Keywords: Executives,Leadership,Mentoring in business,Business consultants; Training of,Study and teaching